2016
DOI: 10.6023/cjoc201604010
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Epoxidation of Olefins Catalyzed by Mn(II, III, V) in Different Valence States

Abstract: The epoxidation catalyzed by transition metals (Cr, Ni, Co, Ru, Mn) has been received widespread attention over the past decades, and the corresponding epoxides are widely used in the synthesis of pharmaceuticals, fine chemicals and pesticides. Compared to other transition metals, metal Mn catalyst has been widely used in organic synthesis due to its inexpensive, environment-friendly, chemical stability and high catalytic activity. This paper reviews the recent progress on epoxidation of olefins catalyzed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In addition, as seen in Figure 4, the electron binding energy of Mn2p 3/2 in catalyst GO-salenMn was 641.4 eV, which was slightly higher than that of Mn2p 3/2 in the homogeneous salenMnCl complex. Thus, the electron cloud density of manganese atoms decreased after support, which was similar with the reported value [8,27], possibly because the micro environment changed after metallic Mn was immobilized with 3-aminopropyl trimethoxy silane and modified GO. A similar observation has also been made for a chiral salenMn III catalyst, which was axially grafted on an amine (-NH 2 ) group modified organic polymer/inorganic zirconium hydrogen phosphate through N-Mn bonding [28].…”
Section: Xps Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, as seen in Figure 4, the electron binding energy of Mn2p 3/2 in catalyst GO-salenMn was 641.4 eV, which was slightly higher than that of Mn2p 3/2 in the homogeneous salenMnCl complex. Thus, the electron cloud density of manganese atoms decreased after support, which was similar with the reported value [8,27], possibly because the micro environment changed after metallic Mn was immobilized with 3-aminopropyl trimethoxy silane and modified GO. A similar observation has also been made for a chiral salenMn III catalyst, which was axially grafted on an amine (-NH 2 ) group modified organic polymer/inorganic zirconium hydrogen phosphate through N-Mn bonding [28].…”
Section: Xps Analysissupporting
confidence: 85%
“…Heterogeneity of homogeneous catalysts is an important strategy to enable the reuse of expensive chiral catalysts and large-scale synthesis [3]. Common catalytic carrier materials include organic polymer, inorganic solidseries, and organic polystyrene/inorganic hydrogen phosphate (Zr, Al, Zn, Ca) [4][5][6][7][8][9][10][11][12][13][14][15]. Unfortunately, immobilized catalysts still have some deficiencies such as low catalytic efficiency and poor reusability.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in epoxidation of olefins has been amplified because it provides a straightforward access to various active epoxides as industrially important intermediates and essential building blocks for everyday chemicals. Epoxides are among the most versatile and tremendously useful precursors in organic synthesis. They are key components for the synthesis of a variety of valuable downstream products such as diols, aminoalcohols, allylic alcohols, ketones, polyethers, etc., which can be further transformed to surfactants, antistatic or corrosion protecting agents, plasticizers, and additives for laundry detergents, lubricating oils, textiles, cosmetics, epoxy resins, and complex molecules used to manufacture air-craft hulls, perfumes, and pharmaceuticals activities. Due to the strain associated with the three membered ring, epoxides are spring-loaded for reactions with different nucleophiles, leading to a wide range of multifunctional organic compounds . Therefore, the catalysis community has been fascinated with prospects of selective synthesis of epoxides by olefin epoxidation. …”
Section: Introductionmentioning
confidence: 99%
“…In our previous works [14,15], the organic polymer-inorganic hydrogen zirconium phosphate, which were frequently functionalized on the benzene ring in the organic component, has been demonstrated to be a versatile support to immobilize the homogeneous chiral MnIII (salen) complex. The corresponding works demonstrated that ZPS-PVPA-based catalyst can effectively catalyze α-methylstyrene and indene, especially α-methylstyrene; the conversion and enantioselectivity are 99%.…”
Section: Introductionmentioning
confidence: 99%